Access to health in an intercultural setting: the role of corpora and images in grasping term variation - Tercedor-Sánchez, Maribel; López-Rodríguez, Clara I. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Medical concepts can often be lexicalized in several ways depending on aspects such as the facet of the concept being underlined or the particular communicative setting in which the concept is being used. This feature of terminology is known as terminological variation. In this paper we consider terminological variation as a tool to improve interlinguistic and intercultural communication, a key issue in the provision of universal access to health care. To facilitate the identification and analysis of terminological variation, the paper also proposes some search strategies to highlight this phenomenon in corpora, the main source of terminological information. Finally, images are proposed as a key issue in the localization process needed to bridge communication gaps between health care providers and lay audiences. The data used in the paper are taken from an international cooperation project aimed at providing health providers in Yucatan, Mexico, with materials and training in intercultural communication for healthcare mainly in Spanish and Mayan, and from a research project on lexical variation .